2015
DOI: 10.4103/1817-1737.165289
|View full text |Cite
|
Sign up to set email alerts
|

Sit-to-stand test and 6-min walking test correlation in patients with chronic obstructive pulmonary disease

Abstract: BACKGROUND:The 6-min walking test (6MWT) is one of the most commonly used tests to assess exercise capacity during chronic obstructive pulmonary disease (COPD). However, it is a relatively time-consuming test. Many authors assessed the usefulness of simpler methods, as the sit-to-stand test (STST), to estimate exercise capacity.PURPOSE:To demonstrate the feasibility of STST, in comparison to 6MWT, for the evaluation of functional status in Tunisian COPD patients and evaluate its correlation to the severity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1
8

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 40 publications
5
32
1
8
Order By: Relevance
“…This is the first study to thoroughly assess the measurement properties of the 1-min STS test in COPD patients. Our findings for cross-sectional validity of the 1-min STS test were in accordance with previous studies that also found moderate to strong correlations (r=0.47-0.75) with the 6MWT [5,15] and with quadriceps strength (r=0.65) [5]. Many measures met our assumptions about strength of correlation, indicating good cross-sectional construct validity; however, the poor change score correlations with exercise capacity tests (<0.4) suggest that they may measure different aspects of exercise capacity that are not correlated over time.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is the first study to thoroughly assess the measurement properties of the 1-min STS test in COPD patients. Our findings for cross-sectional validity of the 1-min STS test were in accordance with previous studies that also found moderate to strong correlations (r=0.47-0.75) with the 6MWT [5,15] and with quadriceps strength (r=0.65) [5]. Many measures met our assumptions about strength of correlation, indicating good cross-sectional construct validity; however, the poor change score correlations with exercise capacity tests (<0.4) suggest that they may measure different aspects of exercise capacity that are not correlated over time.…”
Section: Discussionsupporting
confidence: 93%
“…While the 1-min STS test is increasingly used in studies of COPD patients [8,[10][11][12][13][14][15][16], its learning effect, reliability, responsiveness to change and minimal important difference (MID) have not yet been established in this patient population. Furthermore, little is known about the physiological response to the 1-min STS test in terms of the cardiorespiratory stress elicited.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [10,19,21,22,28,37] have compared the STST with the 6MWT in order to assess its relevance as a tool for evaluation of functional status in COPD patients and healthy subjects. The results obtained by Ozalevli et al in COPD showed a strong correlation between performance in the 1 min-STST and distance walked in the 6-min (r ¼ 0.75, p < 0.001).…”
Section: Stst As Compared With Other Functional Tests In Copdmentioning
confidence: 99%
“…11 The 1-min sit-to-stand (STS) test is a rapid and simple test that is increasingly used in respiratory diseases such as COPD. [12][13][14] The STS movement is frequently performed in daily living and is thought to be a measure of lower-limb strength. The STS test has been recently demonstrated to be reliable and sensitive to intervention in a small sample of adults with CF.…”
Section: Introductionmentioning
confidence: 99%